Ewolucja ekonomii rozwoju - Legiędź, Tomasz (Gospodarka w Praktyce i Teorii, 2013)
The central problem of the economics is to understand the mechanism of economic development. However, there is still no comprehensive theory that would explain the cause of poverty and wealth of nations. The purpose of this article is to analyze an evolution of the economic development paradigm, from the birth of development economics until now, and thus to identify main problems of this branch of economics, and to indicate potential paths for future research.